Phenological synchrony and seasonality of understory Rubiaceae in the Atlantic Forest, Bahia, Brazil - Liuth,Heitor Scarpati (2013)
In tropical forests with low seasonality, climatic variables generally exert a weak influence on the phenology of species. The seasonality of phenophases in closely related taxa can be controlled by phylogenetic constraints in such environments. In this study, our aim was to describe the phenology of Rubiaceae in the understory of the Atlantic Forest in the southern part of Bahia, Brazil, as well as to evaluate the seasonality and phenological synchrony of this family. For two years, we observed 90 individuals belonging to 13 species, in an area of 0.2 ha. Leaf flushing and leaf fall did not demonstrate any seasonality, were continuous for most species and correlated with few of the climatic variables. Flowering was seasonal and correlated positively with all climatic variables. Species exhibited seasonality for this phenophase with high flowering overlap among species of Psychotria, indicating an aggregated pattern for this genus. Fruiting was also seasonal and correlated with all the climatic variables, unripe fruit development peaking at the beginning of the season during which humidity is highest and fruit ripening peaking in the season during which humidity is slightly lower. The vegetative and flowering patterns observed in the study area are commonly seen in other tropical forests. The reproductive seasonality of this family can facilitate the attraction of biotic agents, as postulated in the facilitation hypothesis. Our results demonstrate that climatic variables influenced the phenological patterns observed here, although the high reproductive seasonality and interspecific synchrony, especially in congeneric species, raises the possibility that phylogenetic proximity plays a role in the pattern of the family Rubiaceae.